2021
DOI: 10.1038/s41598-021-99416-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ecological networks and nodes in Fujian province based on green and blue corridors

Abstract: China's Green Space System Planning (GSSP) research has gradually expanded from central urban areas to municipal and provincial scales in recent years. Besides, the research on the role of green space in the water environment has also attracted much attention. However, the study of green corridors usually ignored hydrological data, which widespread absence especially in the large area scale. And the scale of green corridor construction mainly focused on central urban areas. This paper took China's Fujian provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…It is integral to ecosystems and closely linked to human survival and well-being. Recently, the progress of urbanization has not only heightened human-land conflicts and altered LUC patterns but has also exerted a substantial impact on biodiversity [20,52]. Research has demonstrated that the combined use of HQ and LP can comprehensively assess biodiversity changes resulting from LUC alterations, offering novel perspectives and methodologies for biodiversity research.…”
Section: Analysis Of Biodiversity Changementioning
confidence: 99%
See 1 more Smart Citation
“…It is integral to ecosystems and closely linked to human survival and well-being. Recently, the progress of urbanization has not only heightened human-land conflicts and altered LUC patterns but has also exerted a substantial impact on biodiversity [20,52]. Research has demonstrated that the combined use of HQ and LP can comprehensively assess biodiversity changes resulting from LUC alterations, offering novel perspectives and methodologies for biodiversity research.…”
Section: Analysis Of Biodiversity Changementioning
confidence: 99%
“…The habitat quality index (HQI) is frequently utilized as a proxy indicator of biodiversity. It denotes the capacity of a habitat to furnish a stable living environment for organisms on a sustained basis and finds extensive application in biodiversity research [20,21]. It can reflect the biodiversity status of the region to some extent, and the assessment of changes in habitat quality (HQ) can provide a reference for regional LUC management and ecological conservation planning [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Forest ecological corridors represent a vital green framework of urban ecosystems, acting as linear or band-shaped landscape elements. They intricately weave the city's ecological fabric into a cohesive unit [1]. The development of these ecological networks enhances urban accessibility and continuity [2], facilitates species migration, and amplifies the region's ecological service capabilities [3].…”
Section: Introductionmentioning
confidence: 99%
“…Ecological corridors are key ecological lands that ensure connectivity of ecological processes and the completeness of ecological functions. The extraction methods of ecological corridors can mainly be divided into three models: (1) the Minimum Cumulative Resistance model (MCR) [33]; (2) Circuit Theory model [34]; (3) Hydrological Analysis model [35]. Ecological nodes refer to ecological areas on ecological corridors that play a key role in ecological processes between patches [36], and their identification is closely related to the extraction of ecological corridors.…”
Section: Introductionmentioning
confidence: 99%